(untitled) (Stato, Chiese e pluralismo confessionale, 2025)
Practical implications of the Constitutional Court ruling no. 135/2024 which, while not contradicting itself, has (in fact) extended the right of access to medically assisted death SUMMARY: Starting from the Constitutional Court ruling no. 134/2024, the Author addresses the practical implications in the care relationship. After highlighting that the Court has confirmed, in this new ruling, the area of non-punishability of assisted suicide defined by the previous constitutional jurisprudence, he goes into the merits of which are the life-sustaining treatments (TSV) for which there is no definition of either a normative or scientific nature. He then underlines how the Constitutional Court has extensively expanded the perimeter of TSV, thus widening the group of people who can legitimately access medically assisted death. Even if, in order to integrate the principles established by the Constitutional Court ruling no. 242/2019, a whole series of other conditions must be verified, among all the circumstance that their interruption or their non-starting determines the death of the patient in a short period of time. He concludes by observing that compliance with this new limit, due to its very generality, could be the source of different interpretations and unequal treatment, sharing the need for the entire matter to finally be regulated in an organic manner by the Italian Parliament as the Constitutional Court has repeatedly recommended. SOMMARIO: 1. Introduzione - 2. Radicalizzare o elasticizzare il perimetro di tipizzazione dei trattamenti di sostegno vitale (TSV) - 3. Ma qual è (davvero) la ratio della giurisprudenza costituzionale in materia di fine vita? - 4. Conclusioni.